Mortalidade por sepse adquirida na comunidade: uma revisão de escopo - Santos, Danyelle Andrade dos (2025)
Sepsis is a serious global health problem, leading cause of death in non-cardiac ICUs and affecting millions annually. Classified into types such as community acquired sepsis, which has high lethality, its definition has evolved to the current Sepsis-3, focused on organ dysfunction due to dysregulated response to infection. Diagnosis uses scores such as SOFA and qSOFA, and early treatment with antibiotics is crucial, following specific protocols. Given its complexity and the need for data on mortality from community-acquired sepsis in Brazil, continued research is essential. The objective of this study was to map the evidence on mortality from community-acquired sepsis worldwide. This scoping review, conducted according to the JBI guidelines and reported by PRISMA-ScR, sought to map the global evidence on mortality caused by community-acquired sepsis in adults. The guiding question was broad, aiming to identify the panorama of existing research. Inclusion criteria included observational studies, clinical trials and reviews investigating mortality in adults with community-acquired sepsis, without geographical or language restrictions, using mortality rate as the primary outcome. The search was conducted in at least seven databases and Google Scholar, excluding abstracts and publications not focused on community acquired sepsis. A total of 7,502 studies were identified, of which 19 were included in the review. These studies involved 706,607 participants from 15 countries, most of them from observational studies, aged between 53 and 82 years, and with a male predominance. Mortality ranged from 8% to 73%. The most common organ dysfunctions observed were cardiovascular, pulmonary and renal, and prevalent comorbidities included diabetes, cancer and cardiovascular disease. The lung was the main focus of infection, with a predominance of Gram positive bacteria isolated. Most of the studies on sepsis in this review date from 2018 onwards, possibly due to the publication of Sepsis-3 in 2016, which redefined the condition. The concentration of research in North and South America may reflect better infrastructure, funding and prioritization of sepsis, although the economic instability in South America may impact the continuity of studies. Severity scores (SAPS II and APACHE II) also correlate with death. Diabetes, cardiovascular disease and cancer were significant comorbidities. The primary focus of infection was mainly respiratory, followed by abdominal and urinary tract. Microbial etiology indicated higher mortality with Gram-negative (Acinetobacter spp.) and Gram-positive (Streptococcus spp.) bacteria, with mention of antimicrobial resistance. Delayed antibiotic administration (≥6 hours) was a risk factor for higher mortality, reinforcing the importance of early antibiotic therapy in sepsis. Mortality in sepsis is determined by multiple complex factors, including comorbidities, type and site of infection, microorganism, duration of treatment, and severity of organ dysfunction.